Optimal Collision Energy for Higgs Precision Measurements at the ILC250 - Maria Andrea Siddharta; Tian Junping (EPJ Web of Conferences)
In the context of the International Linear Collider, the following research aims to look for the best energies for this machine to work at in order to achieve the most precise measurements on Higgs related quantities. We will firstly focus on the measurement of the Higgsstrahlung cross-section, by carrying out a full model-independent analysis at three different energies, with the aim to minimize the relative error on this quantity. Afterwards, we will set up, in the framework of Effective Field Theories, a toy Lagrangian, and study the precision of anomalous couplings measurements at the energy points aforementioned. In order to do this, we will build up a chi-squared function at each energy point and look at their contours. The chi-squared functions we will construct exploit the new Lorentz structures present in our Lagrangian, making use of the different angular distribution predicted by this theory, and in particular of its energy dependence. We will also take linear combinations of the three chi-squared at the various energy points, aiming to improve our measurements by running the ILC at multiple energies in a short energy range.